2012
DOI: 10.1590/s0080-62342012000400017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do nível de esperança de vida de idosos renais crônicos em hemodiálise

Abstract: O presente estudo teve por objetivo avaliar o nível de esperança dos idosos renais crônicos em hemodiálise, por meio da Escala de Esperança de Herth (EEH). Trata-se de um estudo descritivo transversal, realizado em uma Unidade de Terapia Renal Substitutiva do interior do estado de São Paulo. A amostra foi composta por 50 idosos em tratamento hemodialítico. Após o consentimento em participar da pesquisa, realizou-se entrevistas individuais com os referidos idosos aplicando-se um instrumento de caracterização e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 16 publications
2
10
0
17
Order By: Relevance
“…This shows that male people could be more susceptible to having this disease. (11,12) The average age in this study was 71.1 (±6.8) years. A study carried out in the same geographic region showed that the average age of the participants was 70.0 (±7.5) years.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This shows that male people could be more susceptible to having this disease. (11,12) The average age in this study was 71.1 (±6.8) years. A study carried out in the same geographic region showed that the average age of the participants was 70.0 (±7.5) years.…”
Section: Discussionmentioning
confidence: 78%
“…A study conducted at a Replacement Renal Therapy Unit located in the countryside of Sao Paulo state, with the purpose of characterizing the elderly with chronic kidney disease undergoing hemodialysis and assessing the hope levels through the Herth Hope Scale, identified that it ranged from one and 132 months. (12) Concerning vascular access, 76.7% had the arteriovenous fistula as venous access, which is believed to be the best way of vascular access to perform hemodialysis in elderly people. However, the chances of occurrences and complications resulting from the access in elderly people are in-creased due to the greater vascular frailty, the higher chance of cardiovascular diseases and diabetes and the extensive vascular exploration for previous access.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis is the most common dialysis method that aims to remove liquid and nitrogen patient excreta away for a dialyzer apparatus (also referred to as an artificial kidney) which serves as a synthetic semipermeable membrane, replacing the renal glomeruli and tubules as a filter for compromised kidneys. [2][3] Hemodialysis treatment most often generates frustration and limitations, since it is accompanied by various restrictions, among them maintaining a specific diet linked to water restrictions and change in body appearance due to the presence of the catheter to access vascular or arteriovenous fistula. The multidisciplinary approach to patients who are on hemodialysis process is essential to know all the conditioning factors on the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The multidisciplinary approach to patients who are on hemodialysis process is essential to know all the conditioning factors on the disease. 3 Many professionals do not offer openness to dialogue, acting as absolute masters of truth, disregarding what the patient brings, sometimes judging some patients, not respecting their uniqueness. In this sense, chronic renal patients end up becoming despondent, desperate and often for these reasons or for lack of orientation, they end up abandoning the treatment or not giving importance to the constant care they should have.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation